The Development of Geometric Rows and Sequences Problem-Based Learning with Liveworksheet Media - Jatmiko, Dhanar Dwi Hary; Sunardi, Sunardi; Susanto, Susanto; Suwito, Abi (IKIP Siliwangi, 2023)
The lack of development of Student Worksheets that match what is needed by students can be one of the reasons why many students have difficulty understanding learning materials. This study aims to describe the process and results of the development of the mathematics worksheets based on Problem Based Learning by utilizing liveworksheets on geometric sequences and series material. The type of this research is research and development. This worksheet is designed using Canva and Microsoft Word by utilizing liveworksheets. The subjects of the field trial were 28 students of class XI. This research uses the Four D model from Thiagarajan which consists of the stages of definition, design, development, and dissemination. Data collection methods consist of observation, test, and questionnaire methods. Based on the results obtained from trials in the field, it can be concluded that the mathematics worksheets based on Problem Based Learning by utilizing liveworksheets on geometric sequences and series material met the valid, practical, and effective categories. Other researchers can make maximum use of the features provided on the liveworksheets site because in this study they only utilized a few features and must be alert in anticipating when an error occurs on the site while it is being used.